A quantitative analysis of the impact of job satisfaction on organisational commitment and turnover intention in the post-Covid-19 among university graduates in China - Han, Yutong (2022)
Job satisfaction is regarded as an important organisational variable that has been studied frequently to increase productivity and work quality. Researchers found it has an impact on organisational commitment and turnover intention. College graduates are the major source of the labour market in China. Especially under the influence of COVID-19, China faced significant challenges. It is necessary to understand how the job satisfaction of graduates relates to organisational commitment and turnover intentions. Therefore, organisations could develop appropriate methods to manage college graduates in China during the post-Covid-19. The quantitative method was adopted in this study by focusing on college graduates in China. Through the questionnaire survey on 172 respondents, the data analysis indicated that the job satisfaction of college graduates in China is positively related to organisational commitment and negatively associated with the intention to quit the company. Most importantly, this study found that organisational commitment mediates the relationship between job satisfaction and turnover intention in China context among college graduates.